Learning health system research as a catalyst for promoting physician wellness: EHR InBasket Spring cleaning and team‐based compassion practice - Ming Tai‐Seale; Amanda Walker; Yuwei Cheng; Nathan Yung; Sophie Webb; Ottar Lunde; David Bazzo; Ammar Mandvi; Neal Doran; Gene Kallenberg; Christopher A. Longhurst; Sidney Zisook; et al. (Learning Health Systems)
Abstract Introduction Addressing physician burnout is critical for healthcare systems. As electronic health record (EHR) workload and teamwork have been identified as major contributing factors to physician well‐being, we aimed to mitigate burnout through EHR‐based interventions and a compassion team practice (CTP), targeting EHR workload and team cohesion. Methods A modified stepped wedge‐clustered randomized trial was conducted, involving specialties with heavy InBasket workloads. EHR interventions included quick‐action shortcuts and recommended practice for secure chats. The CTP comprised 30‐s practice between physicians and their dyad partners. Survey and EHR data were collected over four assessment periods. Linear and generalized mixed‐effects models assessed intervention effects, accounting for covariates. Results Forty‐four physicians participated (20% participation rate). While burnout prevalence decreased from 58.5% at baseline to 50.0% at the end of the study, burnout reduction was not statistically significant after EHR (OR 0.43, 95% CI 0.12 to 1.61, p = 0.21) or EHR + CTP (OR 0.60, 95% CI 0.17 to 2.10, p = 0.42) interventions. Statistically significant greater perceived ease of EHR work resulted from both the EHR intervention (coefficient 0.76, 95% CI 0.22 to 1.29, p = 0.01) and EHR + CTP intervention (coefficient 0.80, 95% CI 0.26 to 1.35, p < 0.01). EHR + CTP increased perceived workplace supportiveness (coefficient 0.61, 95% CI −0.04 to 1.26, p = 0.07). Total number of InBasket messages/week increased significantly after EHR interventions (coefficient = 27.4, 95% CI 6.69 to 48.1, p = 0.011) and increased after EHR + CTP (18.5, 95% CI −3.15 to 40.2, p = 0.097). Conclusion While burnout reduction was not statistically significant, EHR interventions positively impacted workload perceptions. CTP showed potential for improving perceived workplace supportiveness. Further research is needed to explore the efficacy of CTP with more participants. The interventions gained interest beyond our institution and prompted consideration for broader implementation.